(3QSGdI aj Yde GdLaQs - (3YHO GdQMef Hf Ydj GdJQjcjs ((3jMji Hf MSjf oeUWai s)
(3ChdgG (B:s
(3CeG HYO ajbhd Yah QHg Gdedjcj YHOGdQMef Ydj GdJQjcj GYde CjOfG Gddg hEjGc HQhM efg EPG CQOJ GSJNQGL GdSDGd ef Gdhab GdoeQHY GdcGed GdCbWGQ s
(3BNQgG (B:s
(3hYdi gPG abS aj LejY gPG GdYe Je Pdc hgPG GdeYehd hGdeYehd Ydjg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3GdehUd (B(86) s
Keywords: (3GdMQha h GdChaGbs